Monitoring System and Hydroponic Plant Automation Using Microcontroller Internet of Things Based (IoT) - Nopi Ramsari; Teddy Hidayat (Compiler, 2022)
Hydroponics is a technique of cultivating plants without using soil media, but using water as a planting medium. Important factors that must be considered in hydroponic plants are plant nutrition, water, temperature, and light intensity. These factors are necessary for hydroponic plants for the growth and reproduction of hydroponic plants. Due to the nutritional needs of hydroponic plants, farmers must take the time to check the concentration of nutrients in hydroponic plants so that the plants can grow well. Therefore, it is necessary to develop new methods of hydroponic farming so that they can grow and develop properly, which can be controlled and monitored automatically. Thus, farmers no longer need to come to agricultural locations. One of the technologies used is technology with the Internet of Things (IoT). This study uses a prototype methodology. For the plant sample used is the lettuce plant. The microcontroller is used as the main controller of all IoT components while the sensors used are the TDS sensor, temperature sensor and light intensity sensor. The research that has been done is IoT technology on hydroponic plants that can monitor and automate plant nutrition settings that are personalized to the needs of hydroponic plants. From the results of testing the IoT tool by reading data from the light intensity and temperature sensors, there is a link between the UV light intensity produced and the water temperature in the hydroponic plant reservoir, that is, the higher the UV light intensity, the higher the water temperature and vice versa. In addition, the other factors are weather and climate conditions around hydroponic plants. IoT data is stored in cloud storage which requires a rental fee.